Flowering characters and relationship with yield of mungbean mutants - Mondal, Mohd Monjurul Alam; Puteh, Adam; Kashem, Md. Abul; Islam, Md. Rafiqul; Nahar, Laila; Berahim, Zulkarami; El-Zeadani, Hassan Hamad Hassan (WFL Publisher, 2014)
The study assessed flowering pattern, reproductive efficiency and their relationship with yield attributes and yield in 15 mungbean mutants/cultivars under sub-tropical condition. Results revealed that the high yielding genotypes produced higher number of flowers, having longer flowering duration than the low yielding ones. It also appeared that the high yielding genotypes had higher rate of flower production than the low yielding ones and the maximum flower production occurred within 15 days after start of flowering. However, low yielding genotypes had higher reproductive efficiency than high yielding ones with few exceptions. Seed yield had significant positive correlation with pod and flower number but had negative relation with reproductive efficiency. Future increase in mungbean yield could be accomplished by developing cultivars which produce high rate of flowers within 15 days after flowering starts with high reproductive efficiency.